Efficient protocol of de novo shoot organogenesis from somatic embryos for grapevine genetic transformation - Capriotti, Luca; Ricci, Angela; Molesini, Barbara; Mezzetti, Bruno; Pandolfini, Tiziana; Piunti, Irene; Sabbadini, Silvia (Frontiers in Plant Science, 2023)
Plant genetic transformation is a powerful tool that can facilitate breeding programs for disease tolerance, abiotic stress, fruit production, and quality by preserving the characteristics of fruit tree elite genotypes. However, most grapevine cultivars worldwide are considered recalcitrant, and most available genetic transformation protocols involve regeneration by somatic embryogenesis, which often requires the continuous production of new embryogenic calli. Cotyledons and hypocotyls derived from flower-induced somatic embryos of the Vitis vinifera cultivars Ancellotta and Lambrusco Salamino, in comparison with the model cultivar Thompson Seedless, are here validated for the first time as starting explants for in vitro regeneration and transformation trials. Explants were cultured on two different MS-based culture media, one having a combination of 4.4 µM BAP and 0.49 µM IBA (M1), and the other only supplemented with 13.2 µM BAP (M2). The competence to regenerate adventitious shoots was higher in cotyledons than in hypocotyls on both M1 and M2. M2 medium increased significantly the average number of shoots only in Thompson Seedless somatic embryo-derived explants. This efficient regeneration strategy, that proposes a combination of somatic embryogenesis and organogenesis, has been successfully exploited in genetic engineering experiments. Ancellotta and Lambrusco Salamino cotyledons and hypocotyls produced the highest number of calli expressing eGFP when cultured on M2 medium, while for Thompson Seedless both media tested were highly efficient. The regeneration of independent transgenic lines of Thompson Seedless was observed from cotyledons cultured on both M1 and M2 with a transformation efficiency of 12 and 14%, respectively, and from hypocotyls on M1 and M2 with a transformation efficiency of 6 and 12%, respectively. A single eGFP fluorescent adventitious shoot derived from cotyledons cultured on M2 was obtained for Ancellotta, while Lambrusco Salamino showed no regeneration of transformed shoots. In a second set of experiments, using Thompson Seedless as the model cultivar, we observed that the highest number of transformed shoots was obtained from cotyledons explants, followed by hypocotyls and meristematic bulk slices, confirming the high regeneration/transformation competences of somatic embryo-derived cotyledons. The independent transformed shoots obtained from the cultivars Thompson Seedless and Ancellotta were successfully acclimatized in the greenhouse and showed a true-to-type phenotype. The novel in vitro regeneration and genetic transformation protocols optimized in this study will be useful for the application of new and emerging modern biotechnologies also to other recalcitrant grapevine genotypes.